MHealth and the management of chronic conditions in rural areas: a note of caution from southern India. Issue 1 (2nd January 2017) - Nahar, Papreen; Kannuri, Nanda Kishore; Mikkilineni, Sitamma; Murthy, G.V.S.; Phillimore, Peter
ABSTRACT: This article examines challenges facing implementation of likely mHealth programmes in rural India. Based on fieldwork in Andhra Pradesh in 2014, and taking as exemplars two chronic medical 'conditions' – type 2 diabetes and depression – we look at ways in which people in one rural area currently access medical treatment; we also explore how adults there currently use mobile phones in daily life, to gauge the realistic likelihood of uptake for possible mHealth initiatives. We identify the very different pathways to care for these two medical conditions, and we highlight the importance to the rural population of healthcare outside the formal health system provided by those known as registered medical practitioners (RMP), who despite their title are neither registered nor trained. We also show how limited is the use currently made of very basic mobile phones by the majority of the older adult population in this rural context. Not only may this inhibit mHealth potential in the near future; just as importantly, our data suggest how difficult it may be to identify a clinical partner for patients or their carers for any mHealth application designed to assist the management of chronic ill-health in rural India. Finally, we examine how the promotion of patient 'self-management' may not be as readily translated to a country like India as proponents of mHealth might assume.